A study into the effects of pyrolysis fuels, pyrolysis conditions and the identification of chemical markers in grapes and wine as smoke taint - Kelly, David Paul (Curtin University, 2014)
Taxonomically distinct vegetation fuels were used to generate smoke for fumigating grapevines to examine the influence of lignin makeup on smoke taint compounds that accrue in wine. Vegetation type had no effect on taint accumulation. Phenol, m-cresol and p-cresol glycoconjugates were closely associated with harsh smoke taint descriptors. While cultivars had similar smoke uptake sensitivity, winemaking method had distinct impact: red winemaking releases 80% of grape phenols compared to 20-35% for white winemaking.